Transformation of Social MSMEs through Participatory Leadership and Strategic Management in Karanggupito Village, Kendal District, Ngawi Regency - Dewi, Sangrila Puspita; Koesoemaningsih, Rachmawati (International Assulta of Research and Engagement (IARE), 2026)
This community service article examines the transformation of social MSMEs through participatory leadership and strategic management in Karanggupito Village, Kendal District, Ngawi Regency. Rural MSMEs often face limitations in inclusive leadership practices and strategic capacity, constraining their sustainability and social impact. The objective of this engagement was to strengthen participatory leadership and strategic management as drivers of organizational and social transformation. Using a Participatory Action Research (PAR) approach, the engagement involved MSME actors as co-researchers through iterative cycles of diagnosis, action, reflection, and evaluation. Data were collected through participatory observation, interviews, surveys, and reflective discussions, and analyzed using thematic analysis and correlation testing. The results demonstrate a significant improvement in participatory leadership practices and strategic clarity, with a strong positive correlation between inclusive leadership and strategic effectiveness. Beyond organizational outcomes, the engagement fostered social cohesion, collaborative networks, and enhanced community legitimacy of MSMEs. The study concludes that PAR-based participatory leadership is a critical mechanism for embedding strategic management within social MSMEs, offering both theoretical and practical contributions to community-based enterprise development.